DIGITAL TRANSFORMATION OF THE CULTURAL HERITAGE OF THE MATARAM KINGDOM - Agung Yuliyanto Nugroho; Sugiarto; Sony Heru Priyanto; Tonny Hendratono; Herra Herryani; Fajar Pradapa (PT. Jurnal Center Indonesia Publisher, 2025)
Digital transformation of cultural heritage is a strategic step in preserving and promoting cultural wealth to present and future generations. This study aims to analyze the digitalization efforts of the cultural heritage of the Mataram Kingdom, both in tangible and intangible forms, and to assess its impact on the preservation and increasing accessibility of cultural information. The research method used is a qualitative study with a descriptive approach through interviews, observations, and documentation studies. The results of the study indicate that the digitization of artifacts, manuscripts, historical sites, and historical narratives of the Mataram Kingdom has made a significant contribution to building public awareness of the importance of cultural preservation. This initiative also opens up opportunities for the development of culture-based ecotourism through digital media, such as applications, interactive websites, and augmented reality. However, challenges such as limited technology, funding, and human resources are still obstacles that need to be overcome through collaboration between the government, academics, cultural communities, and the private sector. Thus, digital transformation is an important means of maintaining the sustainability of the cultural heritage of the Mataram Kingdom in the modern era.